WORLD EXPERIENCE OF FINANCIAL SUPPORT OF INNOVATIVE DEVELOPMENT - I. Kornilova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
This paper examines and summarizes the experience of the financial support of innovative development of the world economy, which occupied a high position in the world economy and demonstrates active dynamics of innovation growth. We consider the financial advantage of direct and indirect actions, which are often used in the practice of the regulation of innovation-studied countries.